Evaluating ChatGPT’s Mandarin “yue” pronunciation system in language learning - Lau, Yoke Lian; Tan, Swee Mee; Abu Bakar, Anna Lynn; Yong, Zi Xian; Yong, Zi Hong; Nasir, Ernahwatikah; Jung Ku, Chen (Institute of Advanced Engineering and Science, 2025)
By incorporating voice control technology into ChatGPT, it becomes possible to engage in conversations or dialogues with individuals who are actively engaged in the process of acquiring language skills. Our study team conducted a modest experiment to evaluate the efficacy of a voice control feedback system in facilitating the mastery of the most challenging pronunciation of the Mandarin syllable